A Review of Malaria Diagnostic Tools: Microscopy and Rapid Diagnostic Test - Anchinmane, Vyankatesh T; Shedge, Rakesh T (Asian Journal of Medical Sciences, 2011)
Objective: Microscopic detection of parasites has been the reference standard for malaria diagnosis for decades. However, difficulty in maintaining required technical skills and infrastructure has spurred the development of non-microscopic malaria rapid diagnostic devices based on the detection of malaria parasite antigen. We evaluated the QDx MALARIA PAN/Pf rapid immunochromatograpic card test by comparing it with the conventional standard blood smear method for the detection of malaria. Material & Methods: A total of 325 specimens of blood from cases of fever (falciparum malaria 88, vivax malaria 168, mixed infection of falciparum and vivax malaria 44, controls 25) were investigated by QDx Malaria Rapid test and blood smear method. Results: The QDx Malaria Rapid test showed 96.6% sensitivity, 100% specificity and 96.9 % accuracy. However, these parameters were lower when the parasitaemia was less than 500 parasites /μL. Conclusion: QDx Malaria Rapid test was found to have enormous advantages over smear examination due to its high degree of sensitivity, specificity, speed and ease of performance. Key Words: Malarial parasite; QDx MALARIA PAN / Pf rapid immunochromatograpic card test; blood smear DOI: 10.3126/ajms.v1i2.2965 Asian Journal of Medical Sciences 1 (2010) 75-79